How thoracic surgeon manage tracheal tumors in African country? (Case series). (August 2019) - Rabiou, Sani; Alami, Badredine; Efared, Boubacar; Lakranbi, Marwane; Harmouchi, Hicham; El-Amrani, Rim; Serraj, Mounia; El-Bouazzaoui, Abderrahim; Ouadnouni, Yassine; Kanja, Nabil; Smahi, Mohamed
Abstract: Introduction: Tracheal tumors are a rare pathological entity whose diagnosis is usually delayed by clinical latency. Surgery, which consists of a tracheal resection-anastomosis with or without reconstructive reconstruction, remains the treatment that ensures the best long-term survival. Methods: This is a retrospective study about 8 patients admitted in the department of thoracic surgery of Hassan II's university hospital of Fes for tracheal tumors management during 7 years time (December 2010 to December 2017). Results: There were 6 men and 2 women with an average age of 44.4 years ranged from 17 to 65 years, 4 were smokers. Dyspnea was the main trigger sign. Seven (7) have undergone bronchial fibroscopy diagnostic with a finding of budding process in 5 patients, the middle of the trachea is often concerned in 3 patients, obstructing the lumen of the trachea in almost all patients. The treatment in all patients was surgical with an intubation via the operative field, 4 trachea resection-anastomosis, 4 plasty (Lateral resection with V plasty, Kergin's plasty, Mattey's tracheobronchial anastomosis and widened V-resection to the carina). The most common histological type in our series was Adenoid Cystic Carcinoma in 2 of our patients. For the other patients we have found squamous cell carcinoma (1 case), adenocarcinoma (1 case), atypical carcinoid tumor (1 case), low grade mucoepidermoid carcinoma (1 case), an adenoma pleomorph (1 case) and endotracheal goiter (1 case). The operative follow-up was simple in 7 of our patients, all of whom underwent post-operative fibroscopy within an average of 9 days. Two cases of post-operative recurrent palsy had been observed, all of which had progressed well under treatment. We have noted 2 deaths, including one at day 4 post-operative, and the other died from complications of post-radiation tracheal stenosis. Back to 32 months' average follow-up, we have enregistered a case of a distant relapse by cervical lymph node metastasis in one patient, 5 years after surgery. Conclusion: Primary tumors of the trachea remain of reserved prognosis with 5-year survival of 57% of all histological types combined. Computed tomodensitometry and tracheobronchial fibroscopy remain the means of reference exploration in the diagnosis and assessment of surgical resectability. Highlights: Primary tumours of the trachea are rare and are usually malignant in adults and benign in children. Benign tracheal tumours are usually misdiagnosed as asthma or chronic. Malignant tumours are often diagnosed earlier than benign tumours and patients thus often present with locally advanced disease. Various surgical techniques can cure primary tumours of the upper airway.